PENGEMBANGAN EKONOMI KREATIF BAGI PENGUSAHA MUDA BERBASIS UMKM WARUNG KOPI HARAPAN MAJU DI KOTA BANDUNG - Atmanegara, Yogi Maulana; Andhika Maulana Rachman; Hendra Anugrah; Amalia Zahara (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
Creative Economy is a concept that suspects creativity and knowledge to be the core values driving the economy. In Indonesia itself, the creative industry has saved the Indonesian economy from sinking during the 1998 currency crisis, and this role has been played by micro, small and medium enterprises (MSMEs). One of the West Java MSMEs engaged in the culinary industry is a medium-sized company in the field of coffee shops based in the city of Bandung called Kedai Kopi Harapan Maju. The purpose of this research is to analyze the development of the creative economy based on coffee SMEs and the supporting and inhibiting factors at the Harapan Maju Coffee Shop. The research method used in this research is qualitative research using descriptive methods and deductive approaches. This type of research is library and field studies. Data collection techniques using three techniques, namely interviews, observation and documentation. The collected data is analyzed starting from all data processing, data presentation and finally drawing conclusions. The results of this study found that the supporting factors for the development of MSME-based creative industries at the Harapan Maju cafe were divided into 2 factors, including internal factors and external factors. Internal factors are the availability of good raw materials and human resources. The external factor is to become a vehicle for learning for everyone who visits the internet cafe. The inhibiting factors for the development of the Harapan Maju coffee-based creative industry are only external factors. The external factor is the unpredictable weather factor at this roadside cafe, especially when it is hit by the latest rain information.